2009
DOI: 10.1176/appi.ajp.2009.09030417
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage and Follow-Up Association Study of Postpartum Mood Symptoms

Abstract: Objective Family studies have suggested that postpartum mood symptoms might have a partly genetic etiology. The authors used a genome-wide linkage analysis to search for chromosomal regions that harbor genetic variants conferring susceptibility for such symptoms. The authors then fine-mapped their best linkage regions, assessing single nucleotide polymorphisms (SNPs) for genetic association with postpartum symptoms. Method Subjects were ascertained from two studies: the NIMH Genetics Initiative Bipolar Disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 46 publications
1
61
0
6
Order By: Relevance
“…There are many reports showing frequent occurrence of maternal transmission of BPD in familial cases (Kato et al 1996;Kornberg et al 2000;Lambert and Gill 2002;Lan et al 2007;Stine et al 1995). This observation has led investigators to hypothesize involvement of the X chromosome, however, several linkage studies failed to detect major genetic factors on the X chromosome and therefore failed to explain parentof-origin effects in mood disorders, including BPD (Gershon and Bunney 1977;Hamshere et al 2009;Mahon et al 2009;Palo et al 2010). Other modes of inheritance that might explain parent-of-origin effects are mitochondrial inheritance and genomic imprinting.…”
Section: Parent-of-origin Effectsmentioning
confidence: 99%
“…There are many reports showing frequent occurrence of maternal transmission of BPD in familial cases (Kato et al 1996;Kornberg et al 2000;Lambert and Gill 2002;Lan et al 2007;Stine et al 1995). This observation has led investigators to hypothesize involvement of the X chromosome, however, several linkage studies failed to detect major genetic factors on the X chromosome and therefore failed to explain parentof-origin effects in mood disorders, including BPD (Gershon and Bunney 1977;Hamshere et al 2009;Mahon et al 2009;Palo et al 2010). Other modes of inheritance that might explain parent-of-origin effects are mitochondrial inheritance and genomic imprinting.…”
Section: Parent-of-origin Effectsmentioning
confidence: 99%
“…While different biological (Albacar et al, 2011;Brummelte & Galea, 2010;Leung & Kaplan, 2009) and genetic (Costas et al, 2010;Mahon et al, 2009;Sanjuan et al, 2008;Treloar, Martin, Bucholz, Madden, & Heath, 1999) factors have been associated with PPD, most researchers have identified a history of affective disorder, depressive episodes and anxiety during pregnancy as the principal risk factors for PPD (O'Hara, 2009;Oppo et al, 2009). Social and psychological factors such as marital discord, low social support, stressful life events and lack of marital support have been strongly associated with PPD in several studies (Beck, 2001;Chen, 2001;O'Hara, 2009), and unemployment, which has been associated with depression in the general population (Stankunas, Kalediene, Starkuviene, & Kapustinskiene, 2006), has been specifically associated with PPD (Chen, 2001;Inandi et al, 2002;Jardri et al, 2006;Lane et al, 1997;Miyake, Tanaka, Sasaki, & Hirota, 2011;Posmontier, 2008;Rubertsson, Wickberg, Gustavsson, & Radestad, 2005;Warner, Appleby, Whitton, & Faragher, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The first genome-wide study of PPD was recently published, and showed that the hemicentin-1 (HMNC1) gene had the strongest association with postpartum mood symptoms. 2 This gene encodes an extracellular protein that contains four estrogen receptorbinding sites and is involved mainly in cell migration, protein anchorage, and the formation of hemidesmosomes in the epidermis. 3 In view of this finding, we genotyped the rs2891230 single-nucleotide polymorphism (TaqManH SNP genotyping assay, Applied Biosystems Inc, Foster City, CA, USA) of the HMCN1 gene using a 7500 Real-Time PCR System (Applied Biosystems Inc, Foster City, CA, USA), in allelic discrimination mode.…”
mentioning
confidence: 99%